The Correlation Between the Type of Occupation Toward Blood Pressure and Cholesterol Levels in Individuals with Hypertension - Yaltafit Abror Jeem; Yanasta Yudo Pratama; Muhammad Luthfi Adnan; Nadia Rachma Nirwingsyah (Universitas Nahdlatul Ulama Surabaya, 2022)
Daily activities and occupation can significantly influence health conditions, so a health assessment related to occupational factors is essential to reduce the risk of the disease. One of the leading causes of mortality from cardiovascular disease worldwide is hypertension. This study aims to determine the correlation between the type of occupation toward blood pressure and cholesterol levels in individuals with hypertension. This paper was an analytical observational study with a cross-sectional approach. The population was individuals with hypertension at Depok 2 Public Health Centre, Sleman Regency, Special Region of Yogyakarta. In addition, the sample was 121 respondents with consecutive sampling. The independent variable was the type of occupation, and the dependent variables were blood pressure and cholesterol levels. Instruments were a questionnaire to evaluate the characteristics of respondents and the type of occupation, a digital sphygmomanometer to examine blood pressure, and cholesterol test kits to assess cholesterol levels. The data analysis used the Chi-Square test with α=0.05. Most respondents were female (59.5%) and aged 60-69 years old (47.1%). They worked in the informal sector (81.2%). In addition, they had grade 1 hypertension (52.1%). There was no significant correlation between the type of occupation and blood pressure in individuals with hypertension (p=0.248). In addition, most respondents had high cholesterol levels (50.4%). Furthermore, there was no significant association between the type of occupation and cholesterol levels in individuals with hypertension (p=0.128). In conclusion, the type of occupation is not a risk factor for increased blood pressure and cholesterol levels in individuals with hypertension.